Question
upstudy study bank question image url

Find \( s \) and \( r \) if \( (x+3) \) is a factor of \( s x^{3}+r^{2} x^{2}-28 x+15 \) and has a remainder of -60 when divided by \( (x-3) \).

Ask by Clark Bob. in Nigeria
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( s = 2 \) and \( r = \pm i\sqrt{5} \).

Solution

Let's solve for \( s \) and \( r \) given the polynomial: \[ P(x) = s x^3 + r^2 x^2 - 28 x + 15 \] We are given two conditions: 1. \( (x + 3) \) is a factor of \( P(x) \). This means \( P(-3) = 0 \). 2. The remainder when \( P(x) \) is divided by \( (x - 3) \) is \(-60\). This means \( P(3) = -60 \). **Step 1: Apply the Factor Theorem** First, substitute \( x = -3 \) into \( P(x) \): \[ P(-3) = s(-3)^3 + r^2(-3)^2 - 28(-3) + 15 = 0 \] \[ -27s + 9r^2 + 84 + 15 = 0 \] \[ -27s + 9r^2 + 99 = 0 \] Divide the entire equation by 9: \[ -3s + r^2 + 11 = 0 \quad \Rightarrow \quad r^2 = 3s - 11 \quad \text{(Equation 1)} \] **Step 2: Apply the Remainder Theorem** Next, substitute \( x = 3 \) into \( P(x) \): \[ P(3) = s(3)^3 + r^2(3)^2 - 28(3) + 15 = -60 \] \[ 27s + 9r^2 - 84 + 15 = -60 \] \[ 27s + 9r^2 - 69 = -60 \] \[ 27s + 9r^2 = 9 \] Divide the entire equation by 9: \[ 3s + r^2 = 1 \quad \text{(Equation 2)} \] **Step 3: Solve the System of Equations** Substitute \( r^2 \) from Equation 1 into Equation 2: \[ 3s + (3s - 11) = 1 \] \[ 6s - 11 = 1 \] \[ 6s = 12 \] \[ s = 2 \] Now, substitute \( s = 2 \) back into Equation 1: \[ r^2 = 3(2) - 11 = 6 - 11 = -5 \] Since \( r^2 = -5 \), then \( r \) is a complex number: \[ r = \pm \sqrt{-5} = \pm i\sqrt{5} \] **Final Answer:** \[ s = 2 \quad \text{and} \quad r = \pm i\sqrt{5} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To find the values of \( s \) and \( r \), we can use the Factor Theorem and the Remainder Theorem. First, since \( (x+3) \) is a factor, we can use the fact that if \( (x+3) \) is a factor of the polynomial, then substituting \( x = -3 \) into the polynomial will yield zero: \[ s(-3)^3 + r^2(-3)^2 - 28(-3) + 15 = 0. \] Calculating this step by step: \[ s(-27) + r^2(9) + 84 + 15 = 0, \] which simplifies to: \[ -27s + 9r^2 + 99 = 0. \] Thus, we have our first equation: \[ -27s + 9r^2 + 99 = 0. \quad \text{(1)} \] Next, we turn to the condition that the polynomial has a remainder of -60 when divided by \( (x - 3) \). According to the Remainder Theorem, we can substitute \( x = 3 \) into the polynomial: \[ s(3)^3 + r^2(3)^2 - 28(3) + 15 = -60. \] Calculating this: \[ s(27) + r^2(9) - 84 + 15 = -60, \] which simplifies to: \[ 27s + 9r^2 - 69 = -60. \] Thus, we have our second equation: \[ 27s + 9r^2 - 69 = -60. \quad \text{(2)} \] Now we can simplify equation (2): \[ 27s + 9r^2 = 9. \] From this, we can divide everything by 9: \[ 3s + r^2 = 1. \quad \text{(3)} \] Now we will solve equations (1) and (3) simultaneously. Starting with (3): \[ r^2 = 1 - 3s. \] We can substitute \( r^2 \) from (3) back into (1): \[ -27s + 9(1 - 3s) + 99 = 0, \] which expands to: \[ -27s + 9 - 27s + 99 = 0. \] This simplifies to: \[ -54s + 108 = 0. \] Solving for \( s \): \[ 54s = 108 \implies s = 2. \] Now substitute \( s = 2 \) back into equation (3) to find \( r^2 \): \[ 3(2) + r^2 = 1, \] which simplifies to: \[ 6 + r^2 = 1 \implies r^2 = 1 - 6 = -5. \] Since \( r^2 = -5 \) yields no real solutions, \( r \) must take on complex values. Therefore: \[ r = i\sqrt{5} \quad \text{or} \quad r = -i\sqrt{5}. \] So the final solution is: \[ s = 2, \quad r = \pm i\sqrt{5}. \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy